Development of students’ character through usrah education as lifelong learning: Case study in the International Islamic University Malaysia - Nik Abdullah, Nik Md. Saiful Azizi; Dollah, Nafi@Hanafi; Awang Marusin, Awang Abdul Muizz (2017)
This paper intends to explain Usrah Mahallah in the International Islamic University Malaysia (IIUM), its roles in developing students’ character and its contributions towards lifelong learning. As the subject matter of this paper is much qualitative, a case study was conducted and so become the sole method of study in order to meet the purpose of this study. 2,323 students participated in Usrah Mahallah for Semester 1, Academic Year 2016/2017, 307 less than the following semester. 70.47 percent of participants managed to attend at least three Usrah sessions organised in Semester 1, 3.45 percent lower than Semester 2. Findings shown that participants of Usrah Mahallah are happy to have Usrah Mahallah as a part of their life as IIUM students. Three factors contributed to such happiness: modern and friendly approaches applied by leaders, organisation of attractive Usrah Mahallah activities at both Mahallah (residential college) and University levels, and conducive environment of Usrah Mahallah inculcated jointly by leaders and participants. Those findings lead to positive implications. Usrah Mahallah is not only regarded as a progressive product of Islamisation in IIUM, but also considered capable in providing students with supplementary social, spiritual and intellectual values which will help IIUM in establishing better community with better social and spiritual state in the future.